Pengembangan Sistem Informasi Distribusi Barang untuk Meningkatkan Efisiensi Rantai Pasok - Hasanah, Uswatun (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2022)
This study focuses on the development and implementation of a Goods Distribution Information System to enhance the efficiency of supply chain management. The system aims to streamline the processes involved in the distribution of goods, from order management to delivery tracking. Key features include real-time inventory monitoring, automated order processing, route optimization, and delivery status updates. By integrating GPS tracking and data analytics, the system ensures accurate and timely information flow, reducing delays and errors in the distribution process. The research outlines the design, development, and deployment phases of the system, including the selection of appropriate technologies, system architecture, and user interface design. The implementation of this system is expected to result in significant improvements in operational efficiency, cost savings, and customer satisfaction. The paper also discusses the challenges faced during development and deployment, as well as the solutions implemented to address these challenges. Results indicate that the Goods Distribution Information System effectively overcomes the limitations of traditional distribution practices and provides a scalable solution for businesses looking to enhance their supply chain operations.